Implementasi Model Taman Ceria Berbasis Multimedia Interaktif untuk Meningkatkan Keterampilan Berpikir Kritis - Pratiwi, Diani Ayu; Octavia , Veniy (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
Students' critical thinking skills become the determining factor of the success of learning activities and student learning outcomes. But the fact is tha activity and critical thinking skills of students are still low which affected on student learning outcomes. From these problems, the combination of the Taman Ceria Model was used in this study to become one of the best solutions. The aim of this study was to describe and analyze students' critical thinking activities. The type of research is Classroom Action Research (CAR). The subjects of this study were fourth grade students of SDN Kuin Selatan 1 Banjarmasin. The type of data in this study is quantitative data obtained through measurement techniques with written tests, and qualitative data obtained by student activities. The results showed that in the critical thinking aspect, students achieved 89% results for the skilled and highly skilled criteria. It can be concluded that the critical thinking aspect of students at each meeting increases and the hypothesis can be accepted. For teachers, this research is expected to be taken into consideration in using learning models in increasing students' critical thinking activities and skills which have an impact on improving student learning outcomes.